Endovascular Repair of a Subclavian Artery Aneurysm With Re-purposed Aorto-Iliac Stent Graft Components - Tomohiro Nakajima; Tsuyoshi Shibata; Yutaka Iba; Nobuyoshi Kawaharada (EJVES Vascular Forum)
Introduction: Subclavian artery aneurysms (SAAs) are rare, and reports on their treatment remain limited. Report: An 83 year old male patient who had undergone endovascular aortic repair (EVAR) for an abdominal aortic aneurysm two years previously was referred to the institution for endovascular treatment of a SAA which he preferred over open surgery. Endovascular repair was undertaken under general anaesthesia and open, access of the right axillary artery with introduction of a 14 F guide sheath; subsequently a 23 × 16 × 100 mm limb graft (Gore Excluder, WL Gore and Associates, Flagstaff, USA) was deployed distally with an additional 23 × 23 × 33 mm proximal cuff (Excluder) with successful SAA exclusion. Discussion: A case of endovascular treatment for a right subclavian artery aneurysm is reported. A successful stent graft from the abdominal EVAR device portfolio was successfully employed.